Second nature : an environmental history of New England - Judd, Richard William (Environmental history of the Northeast., 2014)
"Bounded by the St. Lawrence Valley to the north, Lake Champlain to the west, and the Gulf of Maine to the east, New England may be the most cohesive region in the United States, with a long and richly recorded history. In this book, Richard W. Judd explores the mix of ecological process and human activity that shaped that history over the past 12,000 years."--Provided by publisher